A Union Default: A Policy to Raise Union Membership, Promote the Freedom to Associate, Protect the Freedom not to Associate and Progress Union Representation. (19th June 2018) - Harcourt, Mark; Gall, Gregor; Vimal Kumar, Rinu; Croucher, Richard
Abstract: Workers are defaulted to being non-union in employment relationships across the world. A non-union default likely has substantial negative effects, consistent with the empirical literature reviewed, on union membership levels, because of switching costs, inertia, social norms and loss aversion. A union default would likely have positive effects on union membership, and has the additional virtues of partially internalising the public goods externalities of unions, improving the freedom to associate (the right to join a union) and preserving the freedom not to associate (the right not to join a union). A union default would also strengthen the extent and effectiveness of union representation.